Espacios imaginarios en Plutarco:interpretación místico-literaria de la superficie celeste de la luna (De Facie 94CC-945B) - Pérez-Jiménez, Aurelio (My University, 2014)
Following the line of stilistic interpretation about the Sylla’s Myth in De facie in orbe Lunae I have made in other previous publications (1998, 2002, 2010, and 2011), I propose now to analyse the pages 944C-945B, concerning the celestial surface of the moon. My principal aim in this paper is to underline the lingüistic procedures (fonology, semantic, syntax, morphology etc.) Plutarch uses for enphatizing his reflections on the Moon’s roll concerning the afterlife destiny of man. In this case the spacial topic is the Elysian plain, where the transformation of men into demons and the eventual ascension and fall of his nous to and from the Sun is operated.
Texto de comunicación presentada al X Congreso Internacional de la IPS, celebrado en Delfos (Grecia)
Keywords: Plutarco - Crítica e interpretación; Moralia; De facie in orbe lunae